An Arctic Strait of Two Halves: The Changing Dynamics of Nutrient Uptake and Limitation Across the Fram Strait. Issue 9 (4th September 2021) - Tuerena, Robyn E.; Hopkins, Jo; Buchanan, Pearse J.; Ganeshram, Raja S.; Norman, Louisa; von Appen, Wilken‐Jon; Tagliabue, Alessandro; Doncila, Antonia; Graeve, Martin; Ludwichowski, Kai U.; Dodd, Paul A.; de la Vega, Camille; et al.
Abstract: The hydrography of the Arctic Seas is being altered by ongoing climate change, with knock‐on effects to nutrient dynamics and primary production. As the major pathway of exchange between the Arctic and the Atlantic, the Fram Strait hosts two distinct water masses in the upper water column, northward flowing warm and saline Atlantic Waters in the east, and southward flowing cold and fresh Polar Surface Water in the west. Here, we assess how physical processes control nutrient dynamics in the Fram Strait using nitrogen isotope data collected during 2016 and 2018. In Atlantic Waters, a weakly stratified water column and a shallow nitracline reduce nitrogen limitation. To the west, in Polar Surface Water, nitrogen limitation is greater because stronger stratification inhibits nutrient resupply from deeper water and lateral nitrate supply from central Arctic waters is low. A historical hindcast simulation of ocean biogeochemistry from 1970 to 2019 corroborates these findings and highlights a strong link between nitrate supply to Atlantic Waters and the depth of winter mixing, which shoaled during the simulation in response to a local reduction in sea‐ice formation. Overall, we find that while the eastern Fram Strait currently experiences seasonal nutrient replenishment and high primary production, the loss of winter sea ice and continued atmospheric warming has the potential to inhibit deep winter mixing and limit primary production in the future. Plain Language Summary: The Fram Strait is the main gateway of the Arctic Ocean. In the east, warm, salty waters from the Atlantic flow north into the Arctic basin, and in the west, cold, fresh waters flow south from the central Arctic into the North Atlantic. We examined how changes to the availability of nutrients (which are essential for algae to grow) may limit algae growth in the Fram Strait, both as a result of changes to their source and also how easily the upper ocean mixes nutrients from depth. In the eastern Fram Strait, there is a high availability of nitrate, one of the main nutrients to support algae growth, and winter mixing sustains nutrient supply and biological production in recent decades. However, in the western Fram Strait, the outflowing surface waters do not easily mix with deeper waters and are depleted in nitrate, and nutrient supply from the central Arctic has been declining in recent decades. Our work suggests that although the eastern Fram Strait is sustaining higher levels of algae growth, which supports fisheries and higher trophic levels, warming over the coming decades could shoal winter mixed layers enough to decrease summertime nutrients and limit biological production. Key Points: Nitrate isotope signatures in the western Arctic outflow of Polar Surface Water and eastern inflow of Atlantic Water are characterized Western Fram Strait is strongly stratified and nitrate deplete compared to the east where winter mixing sustains nutrient supply Future warming may shoal the winter mixed layer in the east, decreasing nitrate supply, and reducing primary production below current rates